The Swedish way to parent and play : advice for raising gender-equal kids. - Henkel, Kristina, ....-; Tomicic, Marie, ....- (New York : The Countryman Press, 2020)
Enter a world where Batman does the dishes and Barbie fights crime In the US and around the world, people are striving to close the gender gap. Ranked fifth globally for gender equality, Sweden is doing something right. But to truly close the gap, Swedish experts Kristina Henkel and Marie Tomicic know that we have to start at the beginning, with the daily gender traps and stumbling blocks that cause us to view our children one-dimensionally and limit their potential. In The Swedish Way to Parent and Play, Henkel and Tomicic share practical strategies and tips covering play and friendship, emotions and self-esteem, and language and body, to help parents and teachers support children's development as unique individuals. The point is not that boys should wear dresses and girls can't play with dolls, or that all children should be the same. Gender equality is about variety; it's about showing children 100 possible ways to be instead of just two. Color illustrations throughout